Penerapan Media Layar Digital Interaktif dalam Upaya Peningkatan Keterampilan Menyimak Peserta Didik Inklusi Tingkat SMP - Lestari, Vedra Dita; Aulia, Shafira Rizqi; Ramayanto, Suangga Nur; Ardhianti, Mimas (GERAM, 2025)
Technology is now an important element in education, especially in the provision of interesting and interactive learning media. The ability to listen in Indonesian is very important to understand information. Interactive digital screen media that presents images, text, and sound can increase students' interest and understanding when listening. This study aims to describe the results of the application of interactive digital screen media in an effort to improve the listening skills of inclusion students in grade VIII. This research is a quantitative study with an experimental method using a Single Subject Research (SSR) design. The research subjects are inclusion students in grade VIII who have limitations in understanding the material and learning motivation. The activity was carried out in three sessions at each baseline and intervention condition. The results showed that the baseline condition scores tended to be low (40–50 values) and did not increase significantly. After the intervention using interactive digital screen media, there was a significant increase with the listening score increasing from 70 to 80. Innovation in the use of interactive digital media has proven to be effective in inclusive education, because it is able to provide adaptive, multimodal, and more motivating learning for students with special needs to be actively involved in the learning process.